2016
DOI: 10.1002/glia.23001
|View full text |Cite
|
Sign up to set email alerts
|

The microglial ATP‐gated ion channel P2X7 as a CNS drug target

Abstract: Based on promising preclinical evidence, microglial P2X7 has increasingly being recognized as a target for therapeutic intervention in neurological and psychiatric diseases. However, despite this knowledge no P2X7-related drug has yet entered clinical trials with respect to CNS diseases. We here discuss the current literature on P2X7 being a drug target and identify unsolved issues and still open questions that have hampered the development of P2X7 dependent therapeutic approaches for CNS diseases. It is concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 145 publications
1
151
0
Order By: Relevance
“…Microglial ion channels have recently been identified as potential therapeutic targets in neurological diseases [24, 30, 31], while K + , H + , transient receptor potential (TRP) and Cl - channels have been found to regulate microglial production of ROS [10, 3237]. In this study, we elucidated a novel role of microglial Kir2.1 inward rectifier K + channels, namely regulation of microglial priming processes, which lead to enhanced microglial ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial ion channels have recently been identified as potential therapeutic targets in neurological diseases [24, 30, 31], while K + , H + , transient receptor potential (TRP) and Cl - channels have been found to regulate microglial production of ROS [10, 3237]. In this study, we elucidated a novel role of microglial Kir2.1 inward rectifier K + channels, namely regulation of microglial priming processes, which lead to enhanced microglial ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, enormous effort has been made to develop a number of structurally distinct P2X7 specific antagonists, some of which have been demonstrated to alleviate chronic pain in animal models (Honore et al, 2006a; McGaraughty et al, 2007; Bartlett et al, 2014). However, mechanisms of action for these drugs remain poorly understood, hampering the development of effective therapeutic compounds for human patients (Keystone et al, 2012; Stock et al, 2012; Bhattacharya and Biber, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It has been a consistent finding that activation of P2X7 receptors releases IL-1β and IL-18 from microglia in the brain, although other inflammatory mediators, such as IL-6, may also be released. Thus, P2X7 receptors are intimately involved in neuroinflammation and inhibiting the activation of these receptors has been proposed as a therapeutic method for various diseases in the brain, such as stroke and neurodegenerative diseases, in which neuroinflammation plays a detrimental role (Bhattacharya and Biber, 2016). We and others have shown that IL-1β plays a critical role in anesthesia and surgery-induced cognitive dysfunction (Cao et al, 2012; Cibelli et al, 2010; Lin and Zuo, 2011).…”
Section: Introductionmentioning
confidence: 99%